Analysis Case Control Under-Sanitation and History of Infection Disease with Stunting in Climate-Vulnerable Areas in Indonesia: A Meta-Analysis - Muchsin Riviwanto; Vebby Amellia Edwin; Lindawati; Mahaza; Defriani Dwiyanti; Ricvan Dana Nindrea (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Stunting impacts global health, particularly in low-resource and uncertain climates. Indonesian child stunting, under-sanitation, and infectious disease meta-analysis. Discussion: Unsanitary environments and infectious disease histories are connected to stunting, we found. Food alone does not stunt. Environmental, infectious, and social factors do. Children with a history of infectious diseases had more than double the risk of stunting (pooled OR = 3.72, 95% CI: 2.05–6.73), while those with inadequate sanitation had over three times the chances. Children with inadequate sanitation and a history of infectious disorders were 3.29 times more likely to stunt than those with good sanitation and no infectious diseases. These findings suggest that poor sanitation and infectious diseases induce stunting, especially in harsh regions. Conclusion: Indonesian stunting is caused by climate change, sanitation, and infectious diseases. Ending stunting requires better sanitation, water, and infection control. Future research should examine how disease, hygiene, and climate impact effect. Public health, environmental, and community groups must collaborate to prevent stunting.